A religião produz cidades: relações históricas com a fé e materialização da religiosidade nos espaços públicos em Amaturá - AM - Dias, Luan Cristóvão dos Santos (2020)
The religion, as a mechanism of territorial, ideological and political control, is located in the space for the consolidation of its domain. The city, as an organism composed of its human agents, absorbs the discourses of the imaginary and materializes them in its visible spaces. The present work proposes to draw a dialogical line between religion and city, focusing on the city of Amaturá - AM, which maintains a connection with the Catholic religion that is historical, cultural and identity, massified by the festivals of its patron saints. Focusing on the study of social memory, on the production of religious symbolism and on the connection between man and his physical place of existence, it can understand the ways of existing and (re) signify the city of Amaturá and its public spaces through the discourse of religiosity, a discourse that is propagated by the existence of symbols and by the production of memories, and make the formation of the identity of the Catholic amaturaense be a result of the relationship between religious discourse and the city.